Comparison of Lamotrigine and Oxcarbazepine Monotherapy Among Chinese Adult Patients With Newly-Diagnosed Focal-Onset Epilepsy: A Prospective Observational Study - Chen, Yuncan; Wang, Qinyue; Xu, Ye; Wu, Dongyan; Xu, Lan; Zhu, Guoxing; Wu, Xunyi (Frontiers in Neurology, 2022)
Objective We performed a prospective cohort study to compare the efficacy, safety, effect on mood, and quality of life between lamotrigine (LTG) and oxcarbazepine (OXC) monotherapy among Chinese adult patients with newly-diagnosed focal-onset epilepsy (FOE) with or without secondarily generalized tonic-clonic seizures. Methods We enrolled 106 adult patients with new-onset FOE, of whom 56 were in the OXC group and 50 in the LTG group. Their clinical characteristics were detailly recorded especially basic seizure frequency, seizure types, and drug-related adverse events. Efficacy was evaluated as seizure-free (no seizure for 6 months), effective (seizure reduction by more than 50%), and ineffective (seizure reduction by less than 50%). Both intention-to-treat and per-protocol analyses were performed. We also assessed their mood state with the Zung Self-rating Scale for anxiety (Z-SAS) and Zung Self-rating Scale for Depression (Z-SDS) and quality of life (QOL) with Quality of Life in Epilepsy (QOLIE-31) at their baseline visit, 3-month visits, and 6-month visit. Intra-group comparisons in each group and inter-group comparisons between the two groups were made. Correlation analysis and multiple regression analysis were also conducted. Results Except for gender, the two groups were well matched in any other characteristics such as primary seizure frequency and seizure types. In terms of efficacy, 33 patients in the OXC group were evaluated as seizure-free and 15 as effective, while in the LTG group, 31 were seizure-free, and nine were effective. No significant differences could be observed in efficacy between the two groups (P = 0.429). Through multiple logistic regression analysis, we found that OXC monotherapy was more likely to predict a seizure-free state (OR = 1.76) than LTG, but the difference didn't reach statistical significance (P = 0.322) after correcting for other clinical variables. Both groups had adverse events such as fatigue, drowsiness, dizziness, rash, and gastrointestinal discomfort, most of which were mild and transient. In the OXC group, the scores of SAS (P = 0.067) and SDS (P = 0.004) reduced at the 6-month visit, while the score of QOLIE-31 significantly increased (P = 0.001). In the LTG group, a significant decrease in SAS and SDS scores and an increase in QOLIE-31 scores could be witnessed (All P < 0.001). The inter-group comparison showed that improvement of SAS and SDS in the LTG group was more evident than that in the OXC group, which was of statistical significance. Correlational analysis indicated that the improvement of mood and life quality scales in both groups was independent of baseline seizure frequency and treatment efficacy. Multiple linear regression analysis indicated that LTG monotherapy was the only independent factor that could predict a better SAS (P = 0.01) and SDS (P = 0.019) outcome. Conclusions OXC and LTG are effective as monotherapy and can be considered first-line selection among adult patients with new-onset FOE. Most adverse events are mild, transient, and tolerable. The two drugs improve the mood state of patients, though LTG is superior to OXC in this respect. OXC and LTG have great power in enhancing patients' quality of life. The positive effect on the psychosocial well-being of epilepsy patients may be one of the intrinsic pharmacological properties of LTG and OXC.